Invitro Antibacterial Activity Of Lactobacillus Plantarum Isolated From Soy Milk - P.SRINIVASAN,; K. ASSALAM KHAN,; U.RAJA PERUMAL,; R. VENESH KUMAR,; K. SUGANYA,; M. RAJALAKSHMI, (International Journal of Pharma and Bio Sciences, 2012)
The aim of this study was to determine the Lactobacillus plantarum isolated from soy milk, the antimicrobial activity of the bacteriocin produced by the isolate against the pathogenic bacteria and antibiotic resistance of these isolates.The identity of the culture was based on characteristics of the strains of Lactobacillus spp. as presented in Bergey’s Manual of Determinative Bacteriology, carrying out microscopy (morphology), Gram staining, growth at 15 and 45°C, and fermentation of different carbon sources and growth in 7.5% NaCl. On the basis of all of the identification tests, among fifty three isolates, twenty nine strains isolated from the soymilk were identified as Lactobacillus sps. A total of five among twenty nine were L. plantarum and showed good inhibitory activity against the pathogens. The L. plantarum isolates were resistant to one of the antibiotic discs used in this study. Culture supernatants obtained from the isolates of Lactobacillus spp. exhibited varying degrees of inhibitory activity against strains of Escherichia coli, Staphylococcus aureus, Pseudomonas aeroginosa, Enterobacter cloacae, Bacillus subtilis, Klebsiella pneumoniae, Salmonella typhimurium and Salmonella typhi